Mushrooms from Ghana - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Mushrooms are widely known for their nutritional value. They contain between 21 and 40% protein which compares favourably with soybeans and peas with a dry protein level of about 42%. The average annual yield of an acre of mushrooms in dry protein...